2020
DOI: 10.3390/met10121692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Path on Microstructures and Hardness of Hot-Stamped Steel

Abstract: The final mechanical properties of hot-stamped steel are determined by the microstructures which are greatly influenced by the cooling process after hot stamping. This research studied the effect of the cooling path on the microstructures and hardness of 22MnB5 hot-stamped steel. The cooling path was divided into continuous and discontinuous (primary and secondary) processes. After cooling, the Vickers hardness along the thickness of the specimens was measured. The results indicate that, for a continuous cooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Martensitic steel 22MnB5 was chosen as the experimental material. This material is a typical representative of press-hardened steels, which combines good formability with high strength [19][20][21][22][23][24]. In the automotive industry, these unique material properties are used to reduce BIW while maintaining good crash resistance [25].…”
Section: Methodsmentioning
confidence: 99%
“…Martensitic steel 22MnB5 was chosen as the experimental material. This material is a typical representative of press-hardened steels, which combines good formability with high strength [19][20][21][22][23][24]. In the automotive industry, these unique material properties are used to reduce BIW while maintaining good crash resistance [25].…”
Section: Methodsmentioning
confidence: 99%
“…In Figure 14 are shown the microstructures of two radius samples, 11 and 14, acquired from outer, central and inner regions of the corner. Cold bending has shown to impact the through-thickness microstructure of steels, due to the tensile strain state in outer regions, compressive strain state in inner regions and neutral state in the center, and such behavior has been thoroughly depicted in the literature [48][49][50][51] . On the other hand, studies focused on the microstructural evolution during hot or warm sheet bending are scarce.…”
Section: Microstructure As Affected By the Hot Stamping Processmentioning
confidence: 99%
“…As shown by Lu et al 13 , tempered martensite is morphologically defined by poorly-defined boundaries and a relatively coarse structure as compared with quenched martensite, in addition to the presence of carbides that precipitate as a result of carbon rejection, which can be easily seen in the form of fine white particles. Xu et al 51 associate these particles with carbides. Rezayat et al 34 and Tamizi et al 65 reported that tempering at higher temperatures leads to the formation of coarser carbides, especially in the form of films along the boundaries of martensitic substructures, while tempering at lower temperatures results in the precipitation of finer and more dispersed particles.…”
Section: Rsw Martensite Tempering Simulationmentioning
confidence: 99%
“…This is a consequence of the shifting of the CCT (continuous cooling transformation) curves at higher transformation times. This shift is observed by comparing the CCT curves of 22MnB5 obtained in [16][17][18] and the CCT curves of 37MnB5 described in the work of [18].…”
Section: Physical Simulation Of Thermo-mechanical Press-hardening Cyclesmentioning
confidence: 99%